Interaction of tRNAs with the ribosome at the A and P sites. - Dabrowski, M (1995)
In vitro transcribed tRNA(Phe) analogues from Escherichia coli containing up to four randomly distributed A, G, U or C phosphorothioated nucleotides were used to investigate contact patterns with the ribosome in the A and P sites. The tRNAs were biologically active. Molecular iodine (I2) can trigger a break in the sugar-phosphate backbone at phosphorothioated positions of the ribosomal bound tRNAs if contacts with ribosomal components do not prevent access of the iodine. Highly differentiated protection patterns were found which were strikingly different in the A and P sites, respectively. Strong protections accumulated in the T psi C loop and no protection was seen in the extra-arm region in both sites, whereas the phosphates in the anticodon loop are more strongly protected in the A site. Strong common protections in both the A and P sites were found neighbouring universally or semi-universally conserved bases in prominent regions of the tertiary structure of tRNAs: Y11, Y32, U33, psi55, C56, A58 and Y60. These bases are therefore candidates for 'identity elements' in ribosomal tRNA recognition. The data further indicate that tRNAs change their conformations upon binding to either ribosomal site.